What does attachment have to do with out-of-control sexual behaviour? - Faisandier KM; Taylor JE; Salisbury RM (New Zealand Psychological Society, 2012)
Out-of-control sexual behaviour (OCSB) involves a continuum of sexual behaviour that results in distress or functional impairment. Several factors have been considered relevant to the etiology of OCSB, including attachment style, or the experience of intimacy-related anxiety and/or avoidance (Bowlby, 1969/1982, 1973, 1980). The present study explored OCSB and adult attachment amongst 621 New Zealanders using an online questionnaire. Using the SAST-R (Carnes, Green, & Carnes, 2010) to form groups, the OCSB group (n = 407) reported lower secure and higher insecure adult attachment than the non-OCSB group (n = 214), and this finding was strongest for women. This supports the notion that OCSB is associated with intimacy-related anxiety or avoidance, but further research is needed to clarify the mechanisms of this relationship in terms of whether attachment problems are a cause, consequence, or complex mixture of both in the development and maintenance of OCSB. Such knowledge would contribute to the development of etiological understandings of OCSB and inform future intervention approaches.
Keywords: 1701 Psychology; 1702 Cognitive Sciences